The protective effects of thymol and carvacrol against di (2‐ethylhexyl) phthalate‐induced cytotoxicity in HEK‐293 cells. Issue 8 (6th May 2022) - Amara, Ines; Timoumi, Rim; Annabi, Emna; Ben Othmène, Yosra; Abid‐Essefi, Salwa
Abstract: The protective effects of thymol and carvacrol, two phenolic monoterpenes with a wide spectrum of pharmacological effects, against the oxidative stress produced by the di (2‐ethylhexyl) phthalate (DEHP) in human embryonic kidney cells 293 cells (HEK‐293 cells) were investigated in this study. The cytotoxicity was monitored by cell viability, while oxidative stress generation was assessed by reactive oxygen species (ROS) quantification, antioxidant enzyme activities measurement, glutathione concentration, and malondialdehyde (MDA) quantification. The genotoxicity was evaluated by the measurement of DNA fragmentation through the Comet assay. Our results demonstrated that the pretreatment of HEK‐293 cells with thymol or carvacrol, 2 h before DEHP exposure, significantly increased the cell viability, decreased the ROS overproduction, modulated catalase (CAT), and superoxide dismutase (SOD) activities, restored the reduced glutathione content, and reduced the MDA level. The DNA fragmentation was also decreased by thymol and carvacrol pretreatment. These findings suggest that thymol and carvacrol could protect HEK‐293 cells from DEHP‐induced oxidative stress.